2023
DOI: 10.3389/fpls.2023.1128002
|View full text |Cite
|
Sign up to set email alerts
|

Grapevine bZIP transcription factor bZIP45 regulates VvANN1 and confers drought tolerance in Arabidopsis

Abstract: Drought is a severe environmental condition that restricts the vegetative growth and reduces the yield of grapevine (Vitis vinifera L.). However, the mechanisms underlying grapevine response and adaptation to drought stress remain unclear. In the present study, we characterized an ANNEXIN gene, VvANN1, which plays a positive role in the drought stress response. The results indicated that VvANN1 was significantly induced by osmotic stress. Expression of VvANN1 in Arabidopsis thaliana enhanced osmotic and drough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Annexins belong to a multifunctional protein family that exists in plants, animals and fungi [10]. Recent evidence has shown that plant annexins play critical roles in regulating abiotic and biotic stresses [19,21,25,38]. Our previous study showed that OsANN3 enhances tolerance to drought stress by modulating ABAdependent stress response pathways in rice [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Annexins belong to a multifunctional protein family that exists in plants, animals and fungi [10]. Recent evidence has shown that plant annexins play critical roles in regulating abiotic and biotic stresses [19,21,25,38]. Our previous study showed that OsANN3 enhances tolerance to drought stress by modulating ABAdependent stress response pathways in rice [26].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the overexpression of TdANN12 in tobacco improves drought tolerance through the removal of excess ROS [37]. The heterologous expression of VvANN1 enhances drought tolerance in Arabidopsis by increasing the ROS scavenging activities of SOD, POD and CAT [38]. Therefore, plant annexins have critical roles in drought stress and ROS homeostasis, but how annexins are directly involved in this process remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…bZIP proteins generally contain basic structural domains that bind to specific DNA sequences such as the cis ‐acting elements with ACGT core sequences – A‐box (TACGTA), C‐box (GACGTC) and G‐box (CACGTG)—to regulate the expression of regulatory and functional genes containing the A‐box, C‐box, or G‐box in the promoter (Jakoby et al ., 2002). It has been found that the bZIP family of genes are involved in regulating plant growth and development as well as biotic and abiotic stress responses, including seed maturation ( bZIP10 , bZIP25 , and bZIP53 ; Jain et al ., 2017), flower development ( FD and FDP ; Romera‐Branchat et al ., 2020), salt stress response ( TabZIP15 ; Bi et al ., 2021), cold response ( bZIP68 ; Li et al ., 2022), drought stress response ( bZIP45 and OsbZIP62 ; Yang et al ., 2019; Niu et al ., 2023), cadmium (Cd) stress response ( SpbZIP60 ; Lu et al ., 2022), disease defense ( bZIP10 and APIP5 ; Alves et al ., 2013; Zhang et al ., 2022), and Fe deficiency stress response ( OsbZIP83 ; Kobayashi et al ., 2022). The analysis of cis ‐acting elements in response to Fe deficiency in Arabidopsis and rice, in which a number of bZIP‐binding sequences were identified, suggests the possible involvement of bZIP transcription factors in the plant Fe deficiency stress response (Kakei et al ., 2013; Schwarz et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%